The Influence of Ferromagnetic core, Pick-up Coil Winding Number and Environmental Temperature to the Output Signal of a Fluxgate Magnetic Sensor - Yulkifli Yulkifli; Rahmondia N. S; Mitra Djamal; Khairurrijal Khairurrijal; Deddy Kurniadi (Institut Teknologi Bandung, 2007)
The paper explains some influence parameters of a fluxgate magnetic sensor e.g. number of ferromagnetic cores, number of pick-up coil winding and temperature. The sensors were built in three configurations of pick-up coil winding: 50x2, 60x2, and 70x2 turns, where the excitation coil was kept unchanged at 40x2 turns. The influence of ferromagnetic core and temperature were tested by using the configuration of 60x2 turns. The measurement results show that the increasing of core layer increases the measurement range: ± 100 µT (2 layers), ± 150 µT (6 layers) and ± 200 µT (10 layers). The increasing of pick-up coil winding number increases the sensor sensitivity: 260.64 mV/µT (40/50/40), 321.39 mV/µT (40/60/40) and 383.43 mV/µT (40/70/40). The increasing of temperature shifted the output signal to the higher position